Answer:
last one
Step-by-step explanation:
x = width
x+6 = length
Area = length times width
x(x + 6) =
+ 6x
+ 6<em>x = 114 (subtract 114 from both sides) </em>
<em />
<em> + 6x -114 = 0</em>
Answer:
5322 21 es respusta dissso queridoo burro
Answer:
i hope this works. Feel better soon!
Step-by-step explanation:
1.SAS 2 AAS 3 SAS 4 NOT CONGRUENT 5 SSS 6 ASA
7. ∠BAC≅∠EDC given, BC ≅ CE GIVEN ∠ACB≅∠DCE VERTICAL ANGLES, ΔABC≅ΔDEC AAS
8. ∠PQR≅∠TSR GIVEN R IS MIDPOINT OF PT GIVEN PQ≅ST GIVEN ΔPQR≅ΔTSR HYPOTENUSE LEG THEORUM
9. AC BISECTS BCD GIVEN ∠ABD≅∠ADC GIVEN ∠ACB≅∠ADC BISECTED ANGLES AC≅AC REFLEXIVE PROPERTY OF CONGRUENCE ΔABC≅ΔADC ASA AB≅AC SAME SIDES OF CONGRUENT TRIANGLES
Answer:
The second answer choice is right
Step-by-step explanation:
The real part (-6)
the imaginary part 2i